Between theory and practice: educators’ perceptions on assessment quality criteria and its impact on student learning - Schellekens, Lonneke H.; Kremer, Wim D. J.; Van der Schaaf, Marieke F.; Van der Vleuten, Cees P. M.; Bok, Harold G. J. (Frontiers in Education, 2023)
The shift toward an assessment for learning culture includes assessment quality criteria that emphasise the learning process, such as transparency and learning impact, in addition to the traditional validity and reliability criteria. In practice, the quality of the assessment depends on how the criteria are interpreted and applied. We explored how educators perceive and achieve assessment quality, as well as how they perceive assessment impact upon student learning. We employed a qualitative research approach and conducted semi-structured interviews with 37 educators at one Dutch research university. The data were subsequently analysed using a template analysis. The findings indicate that educators predominantly perceive and achieve assessment quality through traditional criteria. The sampled curricular stakeholders largely perceived assessment quality at the course level, whilst few specified programme-level quality criteria. Furthermore, educators perceived the impact of assessment on student learning in two distinct ways: as a source of information to monitor and direct student learning, and as a tool to prompt student learning. The shift toward a culture of assessment for learning is not entirely reflected in educators' current perceptions. The study's findings set the stage for better assessment quality and alignment with an assessment for learning culture.